The Impact of the SARS-CoV-2 (COVID-19) Pandemic on Gastroenterology Training - Pisani,Anthea (2021)
Abstract: Introduction: The SARS-CoV-2 (COVID-19) pandemic has brought about a radical change in our working patterns. These changes can affect the training that gastroenterology trainees undergo, especially endoscopy since these are aerosol-generating procedures. The aim of this survey was to assess the effect of the COVID-19 pandemic on gastroenterology training across the European countries. Methodology: A questionnaire was set up whereby the different elements of training were analysed. The questionnaire (online) was distributed among trainees through the National Representatives of the European Board of Gastroenterology and Hepatology. Results: In total, 86 trainees (females: 55%; mean age: 32.5 years [SD ±4.57 years]; mean training duration of 2.68 years [SD ±1.63]) from 22 different countries were recruited. From the cohort, 10.5% were considered as vulnerable for acquiring COVID-19. During their job, 4.7% acquired the infection and 26.7% were placed in quarantine. Most trainees noted that their various aspects of gastroenterology training were moderately or severely affected during the initial height of the pandemic: clinical gastroenterology training (67.4%), outpatients (75.5%), didactic teaching (88.3%), multidisciplinary team meetings (65.2%) and endoscopy training (75.6%). Later, when the number of COVID-19-related infections decreased across Europe, the above modalities returned to normal for <50% of the trainees. Conclusion: This European-wide survey has demonstrated that gastroenterology training has been severely impacted during both the initial height of the pandemic and afterwards. Furthermore, the psychological impact on trainees, in terms of training quality, duration and exposure to COVID-19, is unknown. A re-assessment of each centre training programme should be done as to ensure that a high standard of training is still being delivered.